Online Student Peer-Assessment in Higher Education: A Systematic Review of the Literature - Craig, Chris; Kay, Robin (Journal of University Teaching and Learning Practice, 2025)
Peer-assessment is an active process of socially mediated learning that can enhance student learning and metacognitive abilities while developing skills required for success in the modern world. The process has been explored in previous reviews and shown to be valuable through in-person applications. However, a comprehensive review of the literature focusing on online higher education applications has yet to be completed. Our purpose was to conduct a systematic review of the literature on peer-assessment in online higher education classes. Guided by the PRISMA framework, we used a mixed-method integrated methodology to review and synthesize 66 peer-reviewed empirical quantitative, qualitative, and mixed-methods studies published between 2008 and 2023. Following the research context and insight regarding instructional design, two themes emerged: academic impact and student comfort. We identify eight limitations and five recommendations for further research at the end of the paper. The results reflect the context of use along with benefits and challenges related to perceptions of learning, motivation, academic achievement, quality, anonymity, open identification, and time. We provide further context and recommendations for implementation in the discussion section.